Identification of toluene degraders in a methanogenic enrichment culture. Issue 3 (27th June 2014) - Fowler, S. Jane; Gutierrez‐Zamora, Maria‐Luisa; Manefield, Mike; Gieg, Lisa M.
Abstract Methanogenic biodegradation involves the cooperative metabolism of syntrophic bacteria that catalyse the initial attack and subsequent degradation of hydrocarbons, and methanogens that convert intermediates such as hydrogen and carbon dioxide, formate, and/or acetate to methane. The identity of syntrophic microbes and the nature of their interactions with other syntrophs and methanogens are not well understood. Furthermore, it is difficult to isolate the organisms responsible for the initial activation and subsequent degradation of hydrocarbon substrates under methanogenic conditions due to the thermodynamic relationships that exist among microbes in methanogenic communities. We used time‐resolved RNA stable isotope probing and RT‐qPCR to identify the organisms involved in the initial attack on toluene and subsequent degradation reactions in a highly enriched toluene‐degrading methanogenic culture. Our results reveal the importance of a Desulfosporosinus sp. in anaerobic toluene activation in the culture. Other organisms that appear to play roles in toluene degradation include Syntrophaceae, Desulfovibrionales and Chloroflexi. The high bacterial diversity observed in this culture and the extensive labelling of different phylogenetic groups over the course of the stable isotope probing experiment highlight the complexity of the relationships that exist in methanogenic ecosystems.